Food-drug Interactions in Patients with Cardiovascular Diseases - Rudina Prifti (European Scientific Journal, ESJ, 2022)
Cardiovascular diseases are one of the most common diseases in the world. Anticoagulants and other drugs are prescribed as treatment for these diseases however, polypharmacy may increase the risk of drug-drug or food-drug interatrions and decrease patient compliance. Food-drug interatrions may put the patient at risk for serious adverse effects and reduce safety and efficacy of treatment. Food‐drug interaction is a common problem that has occurred as a result of the concomitant use of multiple drugs with food. Food-drug interaction is the term used to describe how a food affects a medication in the body. Food can alter the effectiveness of medication, make unwanted side effects better or worse, or even bring on brand-new negative effects. Drugs may alter how the body processes food. Consumption of foods which contain vitamin K make anticoagulant therapy less effective. On the other hand, patients should be careful when consuming foods like: garlic, ginseng, ginger and ginkgo in order to avoid the undesirable effect of hemorrhage. Healthcare professionals should advice patients taking anticoagulants to be careful with the food they consume and clinicians should manage the time and dose variability of the medicine so a successful therapy can be achieved.